ANALISIS TRANSPARANSI PERTANGGUNGJAWABAN ANGGARAN BADAN PENYELENGGARA PEMILU AD HOC PADA PEMILU 2019 DI KPU KABUPATEN TANJUNG JABUNG BARAT - Sarwani Sarwani; Aidinil Zetra; Hendri Koeswara (REFORMASI, 2022)
The issue of money in elections is a crucial issue, because the realization of elections with integrity is determined by transparency and accountability in election finances. Several studies have found that the elections that have been held in Indonesia have not implemented the principles of transparency and accountability optimally. This study aims to analyze the transparency of the 2019 Election budget accountability by the Ad Hoc EMB’s in Tanjung Jabung Barat Regency. This research is descriptive qualitative with a case study approach. To analyze the data, it is done using the concept of transparency proposed by Koppell (2005). The results of the study indicate that although the budget management activities by Ad Hoc EMB’s have been carried out openly, the information presented in the budget accountability report is not yet fully complete and accurate, so that the implementation of the principle of transparency has not run optimally. This is a consequence of the uneven competence of human resources due to the lack of training related to election finance management. For this reason, it is necessary to increase the competence of human resources through technical guidance or the like to the maximum.